Effect Of Exports, Government Expenditure And Inflation On Indonesia Poverty (2000-2019) - Fadhillah, Anas; Arintoko, Arintoko; Kamio, Kamio (Media Ekonomi, 2021)
The purpose of this study to analyze the effect of exports, government expenditure, and inflation on poverty in Indonesia in 2000-2019, and the independent variables which are the most dominant against poverty in Indonesia. The data used are secondary data taken from Bank Indonesia and Badan Pusat Statistik (BPS). This study uses a regression method with the OLS (Ordinary Least Square) model. or the ordinary least squares model. The results of this study note that oil and gas and non-oil exports have a negative and significant effect on poverty, government expenditure has a significant and negative effect on poverty, and inflation has a positive but not significant effect. To reduce poverty in Indonesia, it is necessary to export commodities that have a large added value, government expenditure which leads to a reduction in the number of poor people, and to control prices of goods and services that are stable / accessible to the poor.